2014
DOI: 10.1097/bor.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies on bone-related outcome and the effect of TNF-α blocking therapy in ankylosing spondylitis

Abstract: Both osteoproliferation (e.g. syndesmophytes and ankylosis of vertebrae) and excessive bone loss resulting in osteoporosis and vertebral fractures are frequently present in AS. Previous studies showed that BMD increases during TNF-α blocking therapy. Long-term follow-up in a large cohort of patients is needed to investigate whether TNF-α blockers can consolidate or stop spinal osteoproliferation and prevent vertebral fractures. Future studies should focus on the effect of these agents on bone-related outcome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Anti-TNF therapy having a positive effect on bone loss in RA was reported by many studies 16,17 . This effect was also reported in AS 8,9,10 . Durnez, et al 10 found that over an average followup of 6.5 years, the increase in BMD was …”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Anti-TNF therapy having a positive effect on bone loss in RA was reported by many studies 16,17 . This effect was also reported in AS 8,9,10 . Durnez, et al 10 found that over an average followup of 6.5 years, the increase in BMD was …”
Section: Discussionsupporting
confidence: 72%
“…In Chopin, et al's research, sCTX was significantly decreased in patients with RA treated with infliximab, but the PINP was stable before and after treatment 18 . While in patients with AS treated with anti-TNF therapy, the sCTX also decreased as in RA, but the PINP significantly increased in our and other studies 8,9,10 . This suggests that when anti-TNF therapy was used in AS, the effect on bone formation was different compared with RA.…”
Section: Rheumatologymentioning
confidence: 43%
See 2 more Smart Citations
“…For clinical purposes, soluble TNFα‐R1 (sTNFα‐R1) with its long‐term bioavailability in stored serum is an optimal proxy of activated TNFα and a biomarker of systemic inflammation. Moreover, clinical data using TNF inhibitors in patients with rheumatoid arthritis (RA) or axial spondyloarthritis (AS) have shown improvements in bone metabolite profiles and decreases in bone loss . Thus, we chose sTNFα‐R1 as a biomarker of inflammation for this study.…”
Section: Introductionmentioning
confidence: 99%